2018
DOI: 10.1016/j.ejvs.2018.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of Clinical Trials Examining the Benefit of Exercise Programmes Using Nordic Walking in Patients With Peripheral Artery Disease

Abstract: This systematic review suggests no benefit of Nordic over standard walking as supervised exercise for PAD. Favourable results were reported for one home based Nordic walking programme. A larger trial is needed to assess whether this finding can be replicated or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In addition to reducing the strength of the lower limb muscles [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], chronic lower limb ischemia also changes the gait pattern. Compared to a group of healthy individuals, people with PAD exhibit an extended stance phase while simultaneously shortening the swing phase [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to reducing the strength of the lower limb muscles [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], chronic lower limb ischemia also changes the gait pattern. Compared to a group of healthy individuals, people with PAD exhibit an extended stance phase while simultaneously shortening the swing phase [8].…”
Section: Discussionmentioning
confidence: 99%
“…Regular physical exercise improves physical fitness, daily functioning, and quality of life in patients with PAD [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…interventions targeting chronic conditions. [20][21][22][23] Due to the interest of NW as an exercise therapy for overweight and obese people, it is important that health and rehabilitation professionals can easily access all existing evidence regarding its effects on this population. Furthermore, it is also essential to have the knowledge on how to accurately prescribe NW programs to meet the requirements of this population, as well as the personal needs and abilities of specific individuals.…”
Section: Introductionmentioning
confidence: 99%
“…We thank Dr. Ian Wee and colleagues for their letter regarding our recent systematic review on Nordic walking for peripheral artery disease. 1 As was pointed out in the review, 1 the findings of prior clinical trials of Nordic walking in patients with peripheral artery disease have varied. One trial reported that patients randomised to a supervised programme of standard walking had better outcomes than those allocated a supervised programme of Nordic walking.…”
mentioning
confidence: 99%
“…As pointed out by Dr. Ian Wee et al some of the treadmill data needed to be converted from time to distance, but this did not have any important influence on the findings of the analysis, as data from six minute walk tests (which did not require conversion) showed similar findings. 1 In general, meta-analyses of multiple randomised trials are considered to provide more reliable evidence than findings from a single randomised trial. As pointed out in the discussion, 1 this meta-analysis does not rule out a small or moderate benefit (or detriment) of Nordic walking vs. standard walking as prior clinical trials have been too small to rule this out.…”
mentioning
confidence: 99%